Barriers to cardiovascular risk prevention and management in Germany – an analysis of the EURIKA study - Schmieder RE; Goebel M; Bramlage P (Vascular Health and Risk Management, 2012)
Roland E Schmieder 1, Matthias Goebel2, Peter Bramlage31Nephrology and Hypertension, University Hospital Erlangen, Germany; 2AstraZeneca GmbH, Medical Department, Wedel, Germany; 3Institut für Pharmakologie und präventive Medizin, Mahlow, GermanyBackground and purpose: Despite the availability of risk engines to determine cardiovascular risk, risk factor control is suboptimal. Using EURIKA data we compared risk factor control in Germany with that of 11 other European countries (rest of Europe [ROE]) to identify differences and opportunities for improvement.Methods: EURIKA was a multinational, cross-sectional study in 12 European countries including Germany from May 2009 to January 2010. Physicians' attitudes to risk factor control based on the 2007 European guidelines on cardiovascular disease (CVD) prevention in a representative cohort of 7641 primary care outpatients aged ≥50 years with no CV disease and at least one major CV risk factor were determined.Results: Compared to the ROE, German physicians were more frequently male (72.7% vs 62.6%), had a higher mean age (51.7 ± 8.4 vs 47.0 ± 9.7 years), faced higher patient loads (37.9% vs 16.5% had >199 patients/week), and involved other health sector professionals (dieticians, psychologists) less (31.8% vs 41.0% in the ROE). The European Society of Cardiology (ESC) guidelines on CVD prevention were more important for German physicians (60.6% vs 55.9%), while those who didn't use them gave reasons for nonuse as too many (62.5% vs 46.2%), too confusing, unrealistic, or not applicable to their patients. Risk engines were used less (54.5% vs 70.7%), with perceived lack of time (65.5% vs 60.2%) a frequent reason for nonuse. Risk factor control in German patients was inadequate (control rates: hypertension 36.3%, dyslipidemia 30.4%, type 2 diabetes 40.6%, obesity 28.8%) but largely comparable to other ROE countries; however, physicians tended to overestimate control rates.Conclusion: EURIKA provides comprehensive data on the status of primary prevention of CVD in clinical practice in Germany and reveals considerable potential for improving the primary prevention of CVD.Keywords: cardiovascular risk factor, primary care